Green Carbon Conference - Basch, G. (2014)
The concept of sustainable development has evolved from a mere movement for the protection of the environment, to other multidimensional approaches. Indeed, today it calls for a holistic approach, seeking to preserve and improve not only the environment, but also to achieve social equity and economic sustainability. In Europe, society demands quality and safe products, not only in the industrial sector but also in agriculture. According to FAO, sustainable agriculture development is a key element of the new global challenges to meet human food security needs at 2050. Unsustainable practices based on intensive soil tillage and agro-chemical applications have increased agri-environmental risks. Whereas world’s food needs are expected to increase by 70% by 2050, agricultural land in Europe will also have to face environmental, economic and social challenges related to sustainable agriculture. As a result, in the EU 2020 Strategy, it is expressed that the new Common Agricultural Policy (CAP) is required to contribute to smart, sustainable and inclusive growth, enhancing social well-being, providing ecosystem services, managing resources sustainably while avoiding environmental degradation. There is broad consensus within the scientific sector that human actions generate a large portion of the greenhouse gas (GHG) emissions, causing global warming. Certainly, Kyoto Protocol states it. According to the European Environmental Agency (EEA), there has been a decrease of 17% in GHG emissions between 1990 and 2009. However, EEA also stressed the importance of the agricultural contribution to total emissions (10.3%). The fossil fuel used in agricultural field operations, along with increasing CO2 emissions from soil through tillage, are considered to be one of the main direct sources of GHG emissions from agriculture sector. Increased inputs required to sustain conventional agriculture also adds significantly to total GHG emissions. Therefore, intensification of production through tillage, agro-chemicals and heavy machinery, which characterizes conventional agriculture in Europe, strongly contributes to increased net GHG emissions instead of mitigating global warming. Sustainable agricultural soil management is crucial for mitigating climate change, especially for the restoration of lost soil organic carbon. In fact, "Agricultural soils management" is recognized as one of the 15 most promising technology options for reducing GHG emissions in the COM (2005) 35 final "Winning the battle against global climate change." The Green Carbon Conference aims to show sustainable management of agricultural soils can help to agriculture mitigate and adapt to climate change, being compatible with the objectives of environmental protection, enhancing biodiversity and supporting farmers’ welfare along with many other environmental, economic and social benefits. Over the last decade, Conservation Agriculture has become known as a set of interlinked agricultural practices, of no or minimum mechanical soil disturbance, maintenance of soil mulch cover, and diversified cropping system, capable of: (a) overcoming several of the severe sustainability limitations of conventional agriculture; and (b) raising productivity, enhancing resilience, reducing degradation and increasing the flow of ecosystem services. The discussion around both the Soil Thematic Strategy initiated in 2002, and the JRC SoCo (Soil Conservation) project clearly recognized the potential of Conservation Agriculture in mitigating and even reversing the problems of soil erosion, soil organic matter decline, soil compaction, loss of biodiversity, climate change vulnerability, among others. Whereas Conservation Agriculture is now practiced successfully on more than 125 million hectares worldwide, Europe has shown to be reluctant with regard to its adoption, despite many promising results confirming its suitability in Europe. Therefore, this European Conference on Green Carbon provides an opportunity to take a leap forward in terms of sharing farmers experiences on Conservation Agriculture across Europe, reviewing the recent progress made in knowledge generation regarding Conservation Agriculture, and to disseminate the outcomes of the currently running LIFE+ Agricarbon (LIFE08 ENV/E/000129). The slogan of ‘Green Carbon’ chosen for this Conference attempts to clarify and highlight the indivisible yet vital link between soil organic carbon and the role that soil health plays in the sustainability of agricultural production and in the flow of ecosystem services. Nevertheless, the topics addressed by the Green Carbon Conference are not only related to the importance of soil organic carbon for the overall soil quality and health, but also include other sustainability issues intimately related to the role of soil carbon such as landscape scale ecosystem functions and services, climate change mitigation and carbon offset, and economic aspects. This Conference also seeks to alert and inform EU policy stakeholders and technical officers of the urgent need to adopt sustainable soil and production practices of Conservation Agriculture to contribute to the objectives of Europe 2020, the EU's growth strategy for the coming decades.